Government alive! - Power, politics, and you - Hart, Diane (Teachers' Curriculum Institute, TCI, 2014)
Section 1 : Power, authority, and government -- Section 2 : Foundations of American government -- Section 3 : Political participation and behavior -- Section 4 : The Legislative Branch -- Section 5 :The Executive Branch -- Section 6 : The Judicial branch -- Section 7 : The United States and the world